Improvement of a legislative and regulatory framework of technology transfer in Ukraine - Mrykhina, Oleksandra (Skhid, 2014)
The article is dedicated to solution of problems of a legislative and regulatory framework of technology transfer in Ukraine. Having analyzed current scientific activities, the author determines that Ukrainian institutional basis of technology transfer related to a legislative and regulatory framework continue to develop and proves that current approaches and recommendations have the fragmentary character. Analyzed scientists consider one or several main legislative acts on technology transfer. Besides, there is no systematic approach to research a phenomenon of regulation of technology transfer at all stages. Taking this into consideration, an aim of the article is to research a legislative and regulatory framework of processes of implementation of technology transfer in Ukraine on a basis of an institutional analysis. To achieve the determined aim the author solved several tasks: legislative and regulatory documents on innovative activity as a general matter and technology transfer are analyzed; inaccuracies, problem areas, and problematic aspects of dedicated legislation are emphasized; intersection of legislative and regulatory acts on technology transfer that causes collisions of legislation is presented; methods and instruments of improvement of a legislative and regulatory framework of technology transfer are substantiated on a basis of the scientific methodology and, especially, an institutional analysis. Research of a legislative and regulatory framework of implementation of technology transfer in Ukraine on a basis of an institutional analysis causes consideration of the mentioned problems as elements of a system of domestic innovative activity development. The author proved that current tendencies of development of Ukrainian legislation on technology transfer and innovative development generally represent worldwide economic processes. Orientation of the state policy of Ukraine on accession to the European Union causes necessity of further adaptation of the Ukrainian legal system to European standards. In a process of development of ways concerning improvement of a legislative and regulatory framework of technology transfer, the author took into account external and internal factors that influenced innovative development of Ukraine.